عبد الحميد مهري ونشاطه السياسي في الخارج 1926-1962 م - العابد، صبرة (جامعة الوادي university of Eloued, 2019)
الملخص: لقد ساعدت البيئة التى نشأ فيها عبد الحميد مهري في تكوين شخصيته,حيث تعتبر عامل مهم من عوامل نبوغه, كما أنإنخراطه في نشاط الثورة التحريرية الخارجي المبكر مكنه من القيام بدورا فعالا في نضال الحركة الاستقلالية داخل الجزائر وخارجها . عمل مهري كوسيط بين الأحزاب السياسية المغاربية قصد توحيد وتنسيق العمل المسلح بينهم ضد الوجود الفرنسي, فبرز كشخصية سياسية محنكة منذ توليه مناصب حساسة داخل حزب حركة الانتصار للحريات الديمقراطية ثم قيادة مكتب جبهة التحرير الوطني بدمشق أدى ذلك الى التوسيع من مهامه ليكون عضوا سياسيا في لجنة التنسيق والتنفيذ ووزيرا لشؤون شمال افريقيا , ثم وزيرا للشؤون الاجتماعية والثقافية في الحكومة الثانية. كما كان له دورا هاما في ترشيد نشاط مكتب المغرب العربي بسوريا , حيث سخر كل جهوده لدعم قضية بلاده, فقد استفادت الثورة التحريرية من أرائه وأفكاره وتوجيهاته التى كان لها دورا جوهريا في حل الكثير من القضايا السياسية وإخراج الثورة من مآزق عديدة . Résumé :انجلزية The environment in which AbdelhamidMehri grew up has created his character, which is an important factor of his genius, and his involvement in the activity of the early external liberation revolution enabled him to play an effective role in the struggle of the independent movement inside and outside Algeria. Mehri worked as an intermediary among the Maghreb political parties in order to unite and coordinate the armed action against the French presence. He emerged as an experienced political figure since taking up sensitive positions within the party of the victory movement for democratic freedoms and then the leadership of the FLN office in Damascus. This led to the expansion of his duties as a political member of the Coordination Committee The Minister of Social and Cultural Affairs of the Second Government. He also played an important role in rationalizing the activity of the Arab Maghreb Office in Syria, where he used all his efforts to support the cause of his country. The liberation revolution benefited from his views, ideas and directives, which played a fundamental role in solving many political issues.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: عبد الحميد مهري; Abdul Hamid Mehri; Abdul Hamid Mehri